TUJUAN PENDIDIKAN DALAM PERSPEKTIF HADIS - Mohammad Al Farabi (Tazkiya: Jurnal Pendidikan Islam, 2020)
The existence of Hadith as a source of teachings conveyed by the Prophet occupies a very important position in providing guidance in determining the direction and goals of education. In many aspects, various Hadiths have given signals and explanations about the importance of shaping the human personality to become a complete Muslim (insan kamil) as the ultimate goal of Islamic Education. Through the content analysis method, ths article aims to explore the content of the Hadith which directs the development of individual basic potentials towards the formation of a complete personality, so that it can help educators and education administrators succeed in delivering students to achieve the true goals of Islamic education.Keywords: Educational Objectives, Hadis, Islamic Education.